Renewed Attention Needed for Prevention of Sudden Unexpected Death in Infancy in the Netherlands - Kanits, Floortje; L'Hoir, Monique P.; Boere-Boonekamp, Magda M.; Engelberts, Adèle C.; Feskens, Edith J. M. (Frontiers in Pediatrics, 2021)
Background: The incidence of Sudden Unexpected Death in Infancy (SUDI), which includes Sudden Infant Death Syndrome (SIDS), has declined in developed countries since the 1980s, including the Netherlands. To identify improvement opportunities in SUDI prevention, we monitored the adherence of parents to the prevention advice on infant care habits over the past 20 years, especially in relation to the SUDI incidence over time. Potential changes in parental adherence between the latest surveys are of specific interest, as these indicate where current focus is needed. Methods: Description of the prevalence of infant care factors related to the risk of SUDI, assessed from five Dutch national surveys from 1999 to 2017 among parents of infants under 12 months, and analysis of the potential differences in these prevalences between the two latest surveys in 2010/11 and 2017 with a z-test. Results: Supine sleeping position decreased from the highest prevalence of 92% in 2010/11, to 83% in 2017. Sleep sack use has increased to 55% in 2017. Avoiding a duvet has remained reasonably stable since 2002/03, and now 95% of parents do not use a duvet. The prevalence of room-sharing, without sharing the bed, increased from 14% in 1999 to the highest prevalence in 2017 (31%). However, also bed-sharing almost doubled from 5.6% in 2010/11 to 10% in 2017. Breastfeeding decreased between 1999 and 2010/11, but increased from 34% in 2010/11 to 42% in 2017. An increased prevalence of mothers who abstained from smoking during pregnancy, as well as both parents not smoking, was observed, although mostly higher educated parents showed this beneficial behavior. Discussion and conclusion: Much has already been achieved first by decreasing prone sleeping since the 80’s, and subsequently promoting supine as the safest sleep position. The decrease in duvet use and smoking, and an increase in breastfeeding have also had impact. Indications of a recent decreased prevalence of the supine sleeping position and higher prevalence of bed-sharing might relate to the slightly increasing SUDI incidence in the Netherlands. Renewed attention for prevention of SUDI and specific advice targeting high-risk groups is needed. Modern, picture driven information via internet is recommended.